PRE-SERVICE TEACHERS’ PERCEPTION ON IMPLEMENTING TECHNOLOGIES IN TEACHING AND LEARNING ENGLISH AT ISLAMIC SCHOOL: English - aryawira pratama (Journal of English Development, 2023)
The world has been completely transformed by technology, and this includes the educational system. Therefore, the goal of this research is to identify the difficulties encountered by pre-service teacher when integrating technology into language teaching and learning English at Islamic school. This research is mainly used a quantitative approach. Ninty pre-service teacher from sixth semester at one of Islamic University in Jambi city were selected as the participants in this research. Questionnaires were used to collect the data, which was then evaluated using a mix method of quantitative and qualitative techniques. The outcome demonstrated the value of using technology in the classroom especially in Islamic school were very useful and helpful. Additionally, more resources and amenities made available by schools are increasingly assisting students in developing their technological proficiency. Although the school has the necessary infrastructure, there have been some issues with integrating technology into the English language learning classes. Additional findings from this research provide policymakers with important information about how to integrate ICT for teaching and learning in the classroom